ISSUES OF FORMING ARTISTIC CULTURE, PICTURE LITERACY - Mambetkadirov , Gayratbay Amanbaevich (Innovative Development in Educational Activities, 2024)
The article is written about the nationality of fine art and the importance of design art, photo art, and practical skills of ikebana compositions in students’ artistic perception of art.